Scanning tomography of SO₂ distribution in a volcanic gas plume - Wright, T; Burton, M; Pyle, D; Caltabiano, T (American Geophysical Union, 2008)
Two-dimensional cross sections of the sulphur dioxide (SO₂) distribution in the volcanic gas plume of Mt. Etna were reconstructed using tomographic techniques. The data for these projections were generated by a network of five automated scanning spectrometers, positioned on the flanks of the volcano. These measure slant-column amounts of SO₂ at 105 different angles, every four minutes. Stable wind conditions allow the plume to be monitored on 82% of days. A time-series of plume cross sections was computed, revealing the potential of this method to track variations in plume position and structure on timescales of minutes to hours, a result of potential importance for air traffic and civil defence om case of eruption, when copious amounts of fine ash can be transported.